Chatbots in Language Classrooms A TAM Analysis on Teachers’ Perspectives - Nazmus Sakib, Munshi; Modina, Rukhsar Raiyan (Journal of NELTA, 2025)
After the emergence of Chat GPT, countries like Bangladesh have seen a dramatic rise  in the integration of a wide array of chatbots in diverse academic and administrative activities at the tertiary level. Although a similar rise can be noted in the expanding body of research exploring students’ utilization of these tools, research initiatives to unravel the teachers’ experiences during this new age of AI integration mostly remain unexplored. Nevertheless, teachers remain one of the key figures in determining the acceptance and penetration of all technological tools in tertiary classrooms. Keeping the Technology Acceptance Model (TAM) in mind, the thematic analysis includes reflections of 16 tertiary-level teachers with an aim to investigate the perceptions developed during the mass  utilization of these tools in the context. Interview transcripts indicate minimal difficulty experienced by research participants while using these chatbots for different administrative and academic activities. They also identify productivity, accessibility, and a reduction of cognitive overload as the rationale behind them leaning toward these possible integration. These findings advocate a revision ofthe existing institutional provisions that do very little in paving the way for technology integration in Bangladeshi classrooms.